PENGETAHUAN PERAWAT TENTANG DEVELOPMENTAL CARE PADA BAYI BERAT LAHIR RENDAH - Hotmayda, Hertaty; Utami, Tuti Asrianti; Wirdani, Paramitha (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
Low birth weight (LBW) infants are infants born with a weight less than or equal to 2500 grams regardless of the infant's gestational age. LBW infants often have difficulty in transitioning from intrauterine to extrauterine. Developmental care can facilitate LBW infants in adapting to their environment. LBW infants have generally treated the Neonatal Intensive Care Unit (NICU) and require a long period of hospitalization due to the immaturity of immunity. Abnormalities in the process of growth and development are frequently in LBW infants and will affect the quality of life. This study aims to determine the relationship between characteristics with the knowledge of nurses about developmental care in LBW infants. Thirty-eight respondents were included. This study uses the quantitative method with the cross-sectional design and descriptive correlation. Data were analyzed using Kendall's Tau B or Tau C. The results of this study showed that There isn't a significant correlation between age and nurse knowledge about developmental care in LBW with p-value 0,429,there isn;t a significant relationship between education and nurse knowledge about developmental care on LBW infants with p-value 0,764, there isn?t a significant relationship between the length of work with the knowledge of nurses about developmental care in LBW infants with p-value 0.134, there isn't a significant relationship between training with knowledge of nurses about developmental care at LBW infants with p-value 0,879.Keywords: developmental care, knowledge, LBW, NICU, nurse